Analysis of Fraud Hexagon Theory in Detecting Fraudulent Financial Statements in Local Governments in West Java Province - Irmawati Rosaeni; Syaiful Rahman Soenaria; Anies Lastiati (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the application of Fraud Hexagon Theory in detecting fraudulent financial statements in local governments in West Java Province. It examines six key elements—pressure, opportunity, rationalization, capability, arrogance, and collusion—both partially and simultaneously to assess their influence on fraud. The study employs a quantitative descriptive approach using secondary panel data from 140 Laporan Keuangan Pemerintah Daerah (LKPD) audited by Badan Pemeriksa Keuangan (BPK) for 2019–2023. Data were analyzed via panel regression with the Common Effect Model (CEM) and Ordinary Least Squares (OLS). Findings reveal that pressure and rationalization negatively and significantly influence fraudulent statements, while opportunity and capability show no significant impact. Conversely, arrogance and collusion exert positive, significant effects and emerge as the dominant fraud drivers. The F-test confirms the collective significance of all Fraud Hexagon variables. These results offer practical implications for regional financial governance: strengthen whistleblowing to combat collusion, monitor officials' public behavior to curb arrogance, elevate Sistem Pengendalian Intern Pemerintah (SPIP) maturity to limit rationalization, and boost fiscal independence to reduce pressure-induced manipulation. The study recommends comprehensive prevention via enhanced internal controls, mandatory ethics training, regular integrity assessments, transparent reporting, and civil society oversight to bolster accountability and transparency.